Structural Transformation and the sophistication of Production - Spatafora, Nikola (IMF Working Papers; Working Paper, 2012)
A new dataset on export sophistication reveals that in many countries the importance of modern services, and the sophistication of manufactured and service exports, has increased over time. However, this trend was less pronounced in LICs. Sophisticated sectors are more likely to act as a catalyst for broad-based economic growth, rather than turning into isolated enclaves, when the economy is liberalized, the exchange rate is not overvalued, and there are good information flows. An educated workforce, external liberalization, and good information flows are important prerequisites for developing sophisticated goods and services. An appropriate macroeconomic policy is particularly important for goods, skilled labor and good information flows for services.